ADOPTION OF JAKARTA'S DIGITAL INNOVATION-BASED CREATIVE ECONOMY POLICY IN MALANG CITY: A LITERATURE STUDY ON STRATEGY AND IMPLEMENTATION - Ayu Nadirah; Moch. Satria Bagus Pradista B.S; Alifiandari Ditha Hapsari (Universitas 17 Agustus 1945 Surabaya, 2026)
The creative economy has become one of the key sectors in driving regional economic growth in Indonesia. However, each city adopts different approaches in managing its development policies. This study aims to compare public policies between Malang City and DKI Jakarta in the context of digital-based creative economy development. The method employed is a narrative literature review with a comparative analysis approach, utilizing secondary data from scholarly journals, policy documents, and official local government reports.The results indicate that DKI Jakarta has established a strong regulatory framework through Governor Regulation No. 106 of 2019, which emphasizes digital governance and financial support for creative economy actors. In contrast, Malang City still focuses on community empowerment through the Malang Creative Center but lacks specific regulations governing the creative economy comprehensively. This difference has led to gaps in digital readiness and institutional coordination. This study underscores the importance of adopting digital-based policies at the regional level to enhance competitiveness and promote inclusivity in Indonesia’s creative economy.